The meaning of 'populism'. (December 2019) - Mueller, Axel
This essay presents a novel approach to specifying the meaning of the concept of populism, on the political position it occupies and on the nature of populism. Employing analytic techniques of concept clarification and recent analytic ideology critique, it develops populism as a political kind in three steps. First, it descriptively specifies the stereotype of populist platforms as identified in extant research and thereby delimits the peculiar political position populism occupies in representative democracies as neither inclusionary nor fascist. Second, it specifies on this basis analytically–normatively the particular stance towards liberal representative democracy (in particular towards popular sovereignty and democratic legitimacy) that unifies populism's political position and explains how populist politics can be compelling for democratic citizens. The normative core (populist ideology) turns out to require no more than two general principles of legitimizing political authority by elections. Surprisingly, it does not need a separate anti-pluralist or exclusionary commitment: it entails it. Third, this normative model allows a response to a contested question in the theoretical discussion, namely, whether populism (properly specified) can be democracy-enhancing. The article defends the negative answer in virtue of the normative core alone and does so as much vis-à-vis a minimal (purely electoral) as vis-à-vis a normatively ambitious (liberal) conception of democracy. The reconstruction of the normative core of populist ideology enables a novel argument to show that populism is incompatible with the continued democratic legitimation of political authority even in the normatively most austere conception of 'electoral democracy', not just with 'liberal democracy'. Assuming a normatively more ambitious concept of democratic legitimation in terms of political autonomy, the model also produces an extremely direct argument showing that populists cannot fulfil their promise of 'taking back control' over political decision-making to the population.